Whole genome analysis of water buffalo and global cattle breeds highlights convergent signatures of domestication - Dutta, P.; Talenti, A.; Young, R.; Jayaraman, S.; Callaby, R.; Jadhav, S.K.; Dhanikachalam, V.; Manikandan, M.; Biswa, B.B.; Low, W.Y.; Williams, J.L.; Cook, Elizabeth A.J.; et al. (Springer, 2020)
More people globally depend on the water buffalo than any other domesticated species, and as the most closely related domesticated species to cattle they can provide important insights into the shared evolutionary basis of domestication. Here, we sequence the genomes of 79 water buffalo across seven breeds and compare patterns of between breed selective sweeps with those seen for 294 cattle genomes representing 13 global breeds. The genomic regions under selection between cattle breeds significantly overlap regions linked to stature in human genetic studies, with a disproportionate number of these loci also shown to be under selection between water buffalo breeds. Investigation of potential functional variants in the water buffalo genome identifies a rare example of convergent domestication down to the same mutation having independently occurred and been selected for across domesticated species. Cross-species comparisons of recent selective sweeps can consequently help identify and refine important loci linked to domestication.